2012
DOI: 10.1194/jlr.p030601
|View full text |Cite
|
Sign up to set email alerts
|

Dietary cholesterol increases paraoxonase 1 enzyme activity

Abstract: This article is available online at http://www.jlr.org High density lipoprotein (HDL) levels have long believed to be cardioprotective ( 1 ) through a variety of processes, including reverse cholesterol transport in which excess cholesterol is taken to the liver for excretion ( 2 ). However, recent studies have highlighted the need to better understand the cardioprotective role of HDL. For example, two recent Mendelian randomization studies found that single nucleotide polymorphisms (SNP) that predict plasma H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 92 publications
1
47
2
2
Order By: Relevance
“…First, although the ESP data contained two coding PON1 functional SNVs ( PON1 Q192 and PON1 L55M ), PON1 -108C/T was not captured by the exome sequencing methods. PON1 -108C/T is a major determinant of PON1 activity, accounting for ‫ف‬ 14% of PON1 activity variance ( 7,20 ). However, as PON1 -108C/T has not been associated with heart disease in meta-analyses ( 8,9 ) or carotid artery disease in smaller cohorts ( 3,6,7 ), and that is found more frequently in AA subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, although the ESP data contained two coding PON1 functional SNVs ( PON1 Q192 and PON1 L55M ), PON1 -108C/T was not captured by the exome sequencing methods. PON1 -108C/T is a major determinant of PON1 activity, accounting for ‫ف‬ 14% of PON1 activity variance ( 7,20 ). However, as PON1 -108C/T has not been associated with heart disease in meta-analyses ( 8,9 ) or carotid artery disease in smaller cohorts ( 3,6,7 ), and that is found more frequently in AA subjects.…”
Section: Discussionmentioning
confidence: 99%
“…One of these hypotheses is that geneby-environment interactions among common SNVs comprise a large portion of heritability ( 18,19 ). Given the wide variety of pharmacologic and dietary determinants on PON1 expression and enzyme activity ( 20 ), the potential interaction of these environmental factors with PON1 variants could represent another important source of trait heritability.…”
Section: Discussionmentioning
confidence: 99%
“…The study population is a subset (n = 1,115) of the previously described CLEAR study ( 8,(10)(11)(12)(40)(41)(42)(43)(44)(45)(46)(47) PLTP region SNP associations with PLTPa. SNPs with у 1% frequency identifi ed in the PLTP region between 50 kb upstream of the fi rst codon or downstream of the last (n = 124 SNPs) were included in our analyses of the genetic predictors of PLTPa.…”
Section: Samplementioning
confidence: 99%
“…On the contrary, in a cohort-based analysis of 1548 humans, Kim et al [38] confirmed that dietary saturated myristic acid and monounsaturated gadoleic acid can positively affect the circulating PON1 activity. It has been also indicated that other dietary compounds such as extra-virgin olive oil, virgin coconut oil, vitamin C, iron and folic acid and dietary cholesterol are positive predictors of the circulating PON1 activity and the possible HDL-C functionality [6,37,44]. Moreover, a significant elevation in the plasma PON1 activity and the HDL-C level has been observed in hypercholesterolemic subjects, in response to anthocyanins at a dose of 160 mg two times daily [97].…”
Section: Effect Of Diet On Paraoxonase 1 and Myeloperoxidase Activitiesmentioning
confidence: 92%